The Utilization of Green Algae into Bioethanol Fuel with Hydrolysis Reaction of Sulfuric Acid - Hilwatullisan; Ibnu Hajar; Zurohaina (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
The increase in population has increased the need for fuel oil and gas, our fossil energy reserve is increasingly decreasing, while its needs continue to increase. This fact opens up a chance to use renewable energy and reduce the use of fossil fuels. In addition to the depletion of the number of fossil fuels, other important reasons for reducing its use are environmental damage issues, ongoing prices, and greater subsidization burden. To overcome the situation, can be pursued in two ways. First reducing the level of consumption and both continue to develop other alternative energy sources, especially renewable energy sources. Lately emerged various findings. Ranging from cassava, sweet potatoes, to corn that is processed into bioethanol. But on its way, the development of the fuel is often burp. The clash with food needs is one of the challenges. While the crop fails and the land needed to be another problem that cannot be underestimated, especially amid the issue of global warming. BioEthanol itself is processed from carbohydrates or starch contained in natural materials. During this time bioethanol is produced by many food crops such as corn, cassava, and sweet potatoes. In fact, these materials are still needed as a support for foodstuffs. Through this study, the author lifted the green algae (Cladophora sp) as one of the alternative solutions in the production of bioethanol which can someday become an alternative fuel. This is because green algae (Cladophora sp) are scattered everywhere and the Carbohydrates content is quite high i.e. 52.54-60.98% (Khuantrairong et al., 2011). In this research researchers utilize the green algae to produce alternative fuels by looking at how the H2SO4 solvent concentration affects the resulting product.